2009
DOI: 10.1016/j.jvs.2008.12.074
|View full text |Cite
|
Sign up to set email alerts
|

Aorto-caval fistula from acute rupture of an abdominal aortic aneurysm treated with a hybrid approach

Abstract: Ruptured abdominal aneurysm is a life-threatening disease requiring immediate treatment. The outcome is even worse in cases complicated by aorto-caval fistula. Treatment is usually attempted by open surgery using direct closure of the venous tear and graft placement in the aorta. Interventional treatment in certain patients seems sensible and has been reported. We report a patient who experienced the rupture of a 13-cm infrarenal aneurysm into the inferior vena cava. He developed signs of severe heart failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 8 publications
0
16
0
3
Order By: Relevance
“…El tratamiento de la FAo-C en la urgencia generalmente es cierre término-terminal de aorta y venorrafia de la VCI 5 . El tratamiento también puede ser híbrido, con implante de endoprótesis en VCI y cierre a cielo abierto de la aorta 6 . Nosotros tratamos al paciente con una endoprótesis a nivel arterial y embolización de una rama de la arteria hipogástrica que alimentaba la fístula.…”
Section: Discussionunclassified
“…El tratamiento de la FAo-C en la urgencia generalmente es cierre término-terminal de aorta y venorrafia de la VCI 5 . El tratamiento también puede ser híbrido, con implante de endoprótesis en VCI y cierre a cielo abierto de la aorta 6 . Nosotros tratamos al paciente con una endoprótesis a nivel arterial y embolización de una rama de la arteria hipogástrica que alimentaba la fístula.…”
Section: Discussionunclassified
“…Although the Immediate Management of the Patient with Rupture: Open versus Endovascular Repair (IMPROVE) aneurysm trial 48 reported that endovascular repair was not associated with significant reduction in 30-day mortality in patients with ruptured AAAs, many proponents feel that if patients can be treated by EVAR, survival is superior. The limiting factor in many cases of open repair for ruptured aneurysms with ACF is that the institution does not offer the appropriate endovascular graft “off the shelf.” Siepe et al 16 presented a hybrid approach in 2009. The patient presented with malperfusion and rapidly deteriorated into shock; 2 aortic stent grafts (Medtronic Inc, Fidley, MN) were placed into the IVC first then after hemodynamics stabilized, transitioned to an open repair.…”
Section: Discussionmentioning
confidence: 99%
“…6 One case report described a patient unsuitable for endovascular aortic repair after which from inside the vein the fistula was covered with a stent graft followed by an open interposition graft of the ruptured aneurysm reducing blood loss significantly. 7 Mortality rates of 30e40% are still favorable compared with retroperitoneal or intraperitoneal ruptured abdominal aortic aneurysm repairs.…”
Section: Discussionmentioning
confidence: 99%